Living displacement : the loss and making of place in Colombia - Celestina, Mateja (New ethnographies., 2018)
Focusing on two cases of resettlement in rural Cundinamarca, Colombia, this book examines how displaced campesinos make sense of their displacement and how displacement shapes their everyday lives.